A Second Prone Dose Algorithm for Patients Undergoing Spinal Anesthesia During Thoracolumbar Surgeries. Issue 3 (28th March 2023) - Wang, Andy Y.; Olmos, Michelle; Ahsan, Tameem; Kanter, Matthew; Liu, Penny; Balonov, Konstantin; Riesenburger, Ron I.; Kryzanski, James
Abstract : BACKGROUND: Spinal anesthesia is safe and effective in lumbar surgeries, with numerous advantages over general anesthesia (GA). Nevertheless, 1 major concern preventing the widespread adoption of this anesthetic modality in spine surgeries is the potential for intraprocedural anesthetic failure, resulting in the need to convert to GA intraoperatively. OBJECTIVE: To present a novel additional prone dose algorithm for when a first spinal dose fails to achieve the necessary effect. METHODS: A total of 422 consecutive patients undergoing simple and complex thoracolumbar surgeries under spinal anesthesia were prospectively enrolled into our database. Data were retrospectively collected through extraction of electronic health records. RESULTS: Sixteen of 422 required a second prone dose, of whom 1 refused and was converted to GA preoperatively. After 15 were given a prone dose, only 2 required preoperative conversion to GA. There were no instances of intraoperative conversion to GA. The success rate for spinal anesthesia without the need for conversion rose from 96.4% to 99.5%. In patients who required a second prone dose, there were no instances of spinal headache, deep vein thrombosis, pneumonia, urinary tract infection, urinary retention, readmission within 30 days, acute pain service consult, return to operating room, durotomy, or cerebrospinal fluid on puncture. CONCLUSION: Use of an additional prone dose algorithm was able to achieve a 99.5% success rate, and those who received this second dose did not experience any complications or negative operative disadvantages. Further research is needed to investigate which patients are at increased risk of inadequate analgesia with spinal anesthesia.